2007
DOI: 10.1136/jnnp.2007.124651
|View full text |Cite
|
Sign up to set email alerts
|

White matter hyperintensities in late life depression: a systematic review

Abstract: Significant differences between early and late onset depression suggest different aetiological mechanisms, in accordance with a theory of "cerebrovascular" depression of late onset. Greater duration of depressive symptoms, signs and treatment does not appear to have a measurable impact on white matter signal in MRI scans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
300
5
10

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 402 publications
(341 citation statements)
references
References 70 publications
17
300
5
10
Order By: Relevance
“…29,31 The relationship of white matter hyperintensities with poor treatment response was evaluated in three studies, with a positive correlation in two of them. 20,30,31 Still, recent meta-analyses showed that these lesions are associated with late-onset depression (vs. early-onset) 35 and also with an increased risk of stroke and dementia, 36 supporting the theory of cerebrovascular disease and depression.…”
Section: Discussionmentioning
confidence: 94%
“…29,31 The relationship of white matter hyperintensities with poor treatment response was evaluated in three studies, with a positive correlation in two of them. 20,30,31 Still, recent meta-analyses showed that these lesions are associated with late-onset depression (vs. early-onset) 35 and also with an increased risk of stroke and dementia, 36 supporting the theory of cerebrovascular disease and depression.…”
Section: Discussionmentioning
confidence: 94%
“…Acredita-se que a hiperintensidade da substância branca cerebral, detectada por ressonância magnética, seja secundária à doença cerebrovascular de pequenos vasos e a alterações neurodegenerativas 46 . Apesar de estudo com autópsia não associar a hiperintensidade da substância branca com envelhecimento patológico 47 , estudos com neuroimagem corroboram a maior prevalência de depressão tardia, comprometimento cognitivo leve, DA, infartos lacunares e menores velocidade psicomotora e flexibilidade cognitiva 21,46,[48][49][50] .…”
Section: Retrogênese Neuropatológicaunclassified
“…Apesar de estudo com autópsia não associar a hiperintensidade da substância branca com envelhecimento patológico 47 , estudos com neuroimagem corroboram a maior prevalência de depressão tardia, comprometimento cognitivo leve, DA, infartos lacunares e menores velocidade psicomotora e flexibilidade cognitiva 21,46,[48][49][50] . A presença de hiperintensidade da substância branca é inversamente proporcional à perfusão cerebral e localiza-se principalmente nas regiões periventriculares e no corpo caloso 32 , sendo o volume dessas alterações estruturais proporcional ao comprometimento cognitivo 48,51 .…”
Section: Retrogênese Neuropatológicaunclassified
“…Among various morphological findings distinguishing LOD from EOD, vascular lesions observed in the subcortical structures are the most consistent and robust abnormality reported in LOD. 8,13,14 Herrmann et al 15 conducted a systematic meta-analysis and concluded that LOD is characterized by more frequent and intense white matter changes, with an odds ratio over 4 for LOD compared with EOD. Greater duration of depressive symptoms, signs, and treatment did not appear to have a measurable impact on white matter signals on magnetic resonance imaging (MRI).…”
Section: Introductionmentioning
confidence: 99%